Quantitative protein expression studies of Malaysia broiler and organic chicken skin - Mohamad Zani, Radiayatul Akma; Muhamad Bunnori, Noraslinda (2014)
Antibiotic treatment is one of the methods used in animal farming. Most of it was given to treat disease and increase growth in animal. Despite its benefit, there are concerns about the residue of antibiotic, due to the health related problems that includes antibiotic resistance and toxicity. Two types of chicken sin samples, which are Broilers(B) and organic chicken (O), were examined by using proteomic strategy. The purpose of this study is to analyse and compare the protein expression of chicken skin between broiler and organic chicken. Chicken samples were homogenized in liquid nitrogen and sample buffer. The supernatant used to determine protein concentration in two types of chicken samples by Braford technique. Then the protein samples were examined by using SDS-PAGE and further resolved by using two-dimensional gel electrophoresis (2D-PAGE). The gels were viewed using GD-800Calibrated Densitometer (Bio-Rad) using Quantity One 1D Analysis software version 4.5 and PD Quest 2D Analysis Software (Bio-Rad). The protein interest spots in second dimensional gel electrophoresis matched to ExPASy SWISS-2DPAGE database as reference to determine what type of protein that were expressed. Results showed that the mean value of protein concentrations in broiler and organic chicken skin were 6.592 ug/uL and 7.296 ug/uL respectively. From the result of 2D-PAGE, protein spotted on gel near pH 4.0 and Mw 50-75 kDa and spot on pH 7.0 and Mw 10-15 kDa was found in different intensity between both samples and predicted as heat shock protein and actin respectively. In conclusion, there were various different of protein expression detected in skin sample between broilers and organic chicken.